2008
DOI: 10.2172/935492
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation limits on antimatter gravitation

Abstract: The proposed Antihydrogen Gravity experiment at Fermilab (P981) will directly measure the gravitational attraction g between antihydrogen and the Earth, with an accuracy of 1% or better. The following key question has been asked by the PAC:Is a possible 1% difference between g and g already ruled out by other evidence?This memo presents the key points of existing evidence, to answer whether such a difference is ruled out (a) on the basis of direct observational evidence; and/or (b) on the basis of indirect evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…For instance, one such argument comes from the absence of anomalies in Eötvös experiments conducted with differing atoms4; the differing number of virtual particle–antiparticle pairs in such atoms might have caused gravitational anomalies to occur. However, all of these arguments are indirect and are not universally accepted11121314; they rely on assumptions about the gravitational interactions of virtual antimatter, on postulates such as CPT invariance, or on other theoretical premises. Although these arguments may well be correct, in a world in which physicists have only recently discovered that we cannot account for most of the matter and energy in the universe, it would be presumptuous to categorically assert that the gravitational mass of antimatter necessarily equals its inertial mass.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one such argument comes from the absence of anomalies in Eötvös experiments conducted with differing atoms4; the differing number of virtual particle–antiparticle pairs in such atoms might have caused gravitational anomalies to occur. However, all of these arguments are indirect and are not universally accepted11121314; they rely on assumptions about the gravitational interactions of virtual antimatter, on postulates such as CPT invariance, or on other theoretical premises. Although these arguments may well be correct, in a world in which physicists have only recently discovered that we cannot account for most of the matter and energy in the universe, it would be presumptuous to categorically assert that the gravitational mass of antimatter necessarily equals its inertial mass.…”
mentioning
confidence: 99%
“…There have not yet been any direct14, free-fall or gravitational balance, tests of the gravitational interactions of observable matter and antimatter. Direct gravitational experiments with non-neutral antimatter, for example, isolated positrons or antiprotons, are exceedingly difficult because the electrical forces overwhelm the gravitational forces17.…”
mentioning
confidence: 99%
“…Fortunately, the exponential 2 The only published direct test so far [4] has yielded the limit −65 <ḡ/g < 110. 3 For example, some authors [39][40][41][42] have suggested that antimatter be identified with the r < 0 solutions of GR's Kerr-Newman equation; in this caseḡ = −g would be the expected GR result. 4 This also suggests a solution to what has been called "the worst prediction in physics": that the gravitational zero-point energy of the universe seems to exceed the size of the cosmological constant by a factor ∼ 10 120 [43].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, there has not yet been any direct experimental observations 4 of the effect of gravity, for example, the gravitational acceleration in the field of the Earth, on antimatter [24,25]. This is perhaps surprising, given that charged antiparticles have been available since the 1930s.…”
Section: Gravitational Interaction Between Matter and Antimattermentioning
confidence: 99%